Antioxidant Potential of Herbal Preparations and Components from Galactites elegans (All.) Nyman ex Soldano - Tebboub, Omar (Evid Based Complement Alternat Med, 2018)
Galactites is a genus of flowering plants belonging to Asteraceae family. This genus is mainly represented by the Galactites elegans (All.) Nyman ex Soldano, the milky thistle, a plant of Mediterranean origin. Galactites elegans is consumed as a monofloral boar thistle honey. Chromatography separation of CHCl(3) and n-BuOH extracts of aerial parts of G. elegans led to isolation of 18 pure compounds. Their structures were elucidated by 1D-and 2D-NMR spectroscopy and confirmed by mass spectrometry analysis. Sinapic aldehyde, abietin, chlorogenic acid, neochlorogenic acid, 8α-hydroxypinoresinol, 9α-hydroxypinoresinol, pinoresinol, 4-ketopinoresinol, nortrachelogenin, and erythro-guaiacylglycerol-β-O-4′-dihydroconiferyl alcohol were isolated from CHCl(3) extract, while luteolin 4′-O-glucuronide, naringenin-7-O-neohesperidoside, kaempferol-3-O-α-L-rhamnopyranosyl-(1→6)-β-D-glucopyranoside, apigenin-7-O-α-L-rhamnopyranosyl-(1→6)-β-D-glucopyranoside, quercitrin, quercetin-3-O-α-L-rhamnopyranosyl-(1→6)-β-D-glucopyranoside, ciwujiatone, and nortrachelogenin-4,4′-di-O-β-D-glucopyranoside were obtained from n-BuOH extract. The majority of isolated compounds displayed a significant antioxidant potential in vitro test (DPPH). The ability of compounds to reduce the level of peroxides in control and BHP-treated Jurkat cells was studied. The lignan derivatives were also able to reduce at 50 μM the basal level of peroxides in Jurkat cells as well as counteract peroxide increase induced by BHP treatment. Particularly 8α-hydroxypinoresinol was the most active showing 70% of peroxide level inhibition.